Odwracanie znaczeń i zacieranie granic jako narzędzie sprawowania współczesnej władzy - Polak, Ewa (Fides, Ratio et Patria. Studia Toruńskie, 2018)
The blurring of the previous lines, changing meanings and assessment criteria, the shortening of the distance between dissimilarities accompanies the contemporary world’s transformation. The distinction between the extremes, among others between fiction and reality, the truth and the lie, good and evil is more and more difficult to recognize. It is the consequence of globalization, promoting the principles of neo-liberal market economy, economization of all spheres of live, growing role of mass media influence and development of manipulative techniques impact on people. It results many effects, for example: dehumanization and commercialization of human relationships and cultural patterns, erosion of borders and disappearance of the sphere of the sacred and taboo and good and evil., confusion and disintegration of people, shaping people without their own views, values, beliefs, personalities.